Trajetórias internacionais: lealdade à instituição de ensino superior na perspectiva da mobilidade acadêmica internacional - Carrapato, Ana Claudia (2024)
The relationship between students and institutions of higher education (IES) has been extensively researched across multiple dimensions, primarily focusing on the discernment of quality, satisfaction, and trust from students towards their respective institutions. This thesis aims to delve into the intricacies of the relationship dynamics and loyalty between students and IES, particularly through the lens of their involvement in international academic mobility programs facilitated by these institutions. To elucidate this, a comprehensive literature review encompassing empirical articles up until December 2023 was undertaken alongside a qualitative research approach. The research corpus comprises 18 in-depth interviews conducted with students who partook in international academic mobility during the year 2022. The findings underscored the pivotal role of international academic mobility in fostering student loyalty towards the IES. Perceived benefits by students have solidified bonds between both entities, thereby amplifying the ethos of lifelong learning within the institutional framework. This study contributes to the advancement of current models for assessing student loyalty to IES by identifying and corroborating international academic mobility as a salient antecedent in cultivating institutional loyalty. Furthermore, it furnishes educational administrators with invaluable insights to steer their efforts towards crafting mobility programs endowed with coveted attributes that can precipitate tangible impacts on the human and professional development trajectory of students within the institutional milieu.